2009
DOI: 10.1525/cond.2009.080094
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Reproductive Demands in a Dynamic Upwelling System: Foraging Strategies of a Pursuit-Diving Seabird, the Marbled Murrelet

Abstract: Resumen. Las aves marinas mantienen una plasticidad en sus comportamientos de forrajeo para poder con las demandas energéticas y las restricciones de forrajeo que varían durante el ciclo reproductivo. Sin embargo, los estudios sobre comportamiento que comparan individuos reproductivos y no reproductivos son raros. Aquí caracterizamos cómo los individuos de la especie Brachyramphus marmoratus ajustan sus esfuerzos de forrajeo en respuesta a sus demandas reproductivas en un sistema de surgencias marinas en el ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Kittlitz's murrelet abundance appeared to be highest earlier in the day and during the incoming high tide phase. This daily pattern is similar to that ob ser ved in studies of the congeneric marbled murrelet (Speckman et al 2000, Peery et al 2009). Increased abundance and activity during morning hours could indicate that Kitt litz's murrelets are responding to the diurnal movements of potential prey species that feed at the surface at night and migrate to inaccessible water depths during daylight hours; these species may be most sus- ceptible to predation during these transition periods (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Kittlitz's murrelet abundance appeared to be highest earlier in the day and during the incoming high tide phase. This daily pattern is similar to that ob ser ved in studies of the congeneric marbled murrelet (Speckman et al 2000, Peery et al 2009). Increased abundance and activity during morning hours could indicate that Kitt litz's murrelets are responding to the diurnal movements of potential prey species that feed at the surface at night and migrate to inaccessible water depths during daylight hours; these species may be most sus- ceptible to predation during these transition periods (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Many predators rely on herring when they move inshore around spawning season. Many crustaceans (Hines 1982, Stone andO'Clair 2001), echinoderms (Mattison et al 1976, Cieciel et al 2009), rockfishes and lingcod (Jorgensen et al 2006, Mitamura et al 2009, Tolimieri et al 2009, Beaudreau and Essington 2011, Green and Starr 2011, Freiwald 2012, harbor seals (Peterson et al 2012, Ward et al 2012, some seabirds (Peery et al 2009, Barbaree et al 2015, Lorenz et al 2017, and some flatfishes (Moser et al 2013), exhibit restricted patterns of movement and are likely to exploit one to several major subpopulations, but generally not the entire spatial distribution of the metapopulation (stock). In contrast, humpback whales (Dalla Rosa et al 2008, Kennedy et al 2014), orcas (Hauser et al 2007, Fearnbach et al 2014, some seabirds (Pearce et al 2005), sea lions (Merrick and Loughlin 1997, Fearnbach et al 2014, Kuhn and Costa 2014, fur seals , halibut (Loher 2008, Seitz et al 2011, Nielsen et al 2014, and gadiforms (Wespestad et al 1983, Hanselman et al 2014, Rand et al 2014 can, given ranges reported, access the geographic area covered by the stock (Table 4, see DataS1: Home_Range_Literature).…”
Section: Insights Into the Benefits Of Population Portfolios To Managmentioning
confidence: 99%
“…Thus, it seems unlikely that murrelets were negatively affected by handling in our study compared to other studies that used telemetry to estimate breeding propensity. Yet another consideration is that transmitter weight negatively affected murrelet breeding propensity because transmitters in our study were 0.3-1.4 g heavier (3.3 g total) than those used in past studies (transmitter weight range ¼ 1.9-3.0 g; Hull et al 2001, Bradley et al 2004, Kuletz 2005, McFarlane Tranquilla et al 2005, Hebert and Golightly 2008, Peery et al 2009, Barbaree et al 2014. Vandenabeele et al (2012) theorized that transmitter weight may disproportionally negatively affect alcids compared to other seabirds.…”
Section: Murrelet Breeding Propensitymentioning
confidence: 60%
“…Thus, marbled murrelets have been the focus of numerous space use studies. These studies have measured marine range size Golightly 2008, Barbaree et al 2015), marine movements (Kuletz 2005, Hebert and Golightly 2008, Peery et al 2009), and nest-sea commuting distances (Whitworth et al 2000, Hull et al 2001, Kuletz 2005, Barbaree et al 2015 to identify important factors for sustaining populations. Notably, however, there have been no published studies on space use by murrelets in Washington, where declines have been observed (Miller et al 2012, Falxa and.…”
mentioning
confidence: 99%